2011
DOI: 10.1055/s-0031-1285888
|View full text |Cite
|
Sign up to set email alerts
|

Rückkehr zur Arbeit – Erfahrungen und Erwartungen von Patientinnen und Patienten in der stationären onkologischen Rehabilitation

Abstract: The results indicate that after having received their diagnosis most cancer patients do not experience negative reactions from their work environment and consequently report few worries with regard to returning to work. The different views on work-related offers during rehabilitation indicate that the concepts of occupation-related therapies within cancer rehabilitation might be optimized by taking the different needs of male and female patients into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…The immediate conditions in the workplace and the support provided for the return to work are a crucial promoting factor. The cancer survivor is more likely to be permanently able to work if he or she is integrated into the social network at the workplace, the employer ensures working conditions that are beneficial to his or her health, and professional help is offered in the return to working life, than if these factors are absent or even their opposite is true (5,15,(24)(25)(26)(27).…”
Section: Returning To Work After Cancermentioning
confidence: 99%
“…The immediate conditions in the workplace and the support provided for the return to work are a crucial promoting factor. The cancer survivor is more likely to be permanently able to work if he or she is integrated into the social network at the workplace, the employer ensures working conditions that are beneficial to his or her health, and professional help is offered in the return to working life, than if these factors are absent or even their opposite is true (5,15,(24)(25)(26)(27).…”
Section: Returning To Work After Cancermentioning
confidence: 99%
“…In different studies and our own investigations, it could be demonstrated that especially patients between 40 and 60 years and patients with a low school education and with moderately severe to heavy physical load in their occupation are threatened by the financial and social burden [4,5,7,[14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…If good conditions for integration in the social structure at the job and good terms of employment are created and if professional help is provided during the process of resumption of the professional activity, the likelihood of a successful RTW is much higher than if these factors are not given [5,7,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Berufliche Gründe spielten aufgrund der geringen Anzahl noch berufstätiger Patienten ohne Reha-Inanspruchnahme (N = 34) bei den Nennungen eine untergeordnete Rolle. Die beruflichen Grün- [26]. Gerade in diesem Zusammenhang könnte den Patienten vermittelt werden, dass die Rehabilitation hilft, den Einstieg in die Arbeit zu erleichtern.…”
Section: Diskussionunclassified